Sanguinarine highly sensitises breast cancer cells to doxorubicin-induced apoptosis - du Plessis, Manisha; Fourie, Carla; le Roux, Heloise; Engelbrecht, Anna-Mart (South African Journal of Science, 2024)
Breast cancer is the most commonly diagnosed cancer and the second most common cause of cancer death in women. The anthracycline, doxorubicin, is a well-known and highly effective treatment for breast cancer patients; however, many patients present with resistance to chemotherapeutic drugs, which ultimately results in treatment failure and contributes to high mortality rates. It is well established that the mitogen-activated protein kinase phosphatase 1 (MKP-1) mediates the response to chemotherapy, where upregulated MKP-1 is associated with chemoresistance. We investigated whether MKP-1 inhibition or silencing can sensitise triple-negative MDA-MB-231 breast cancer cells to doxorubicin therapy. We found that MKP-1 inhibition and silencing sensitises breast cancer cells to doxorubicin-induced apoptosis. Additionally, the inhibition of MKP-1 in combination with doxorubicin treatment promotes autophagy induction, while doxorubicin and not MKP-1 modulation increased lysosomal acidic compartments. As such, this study demonstrated that MKP-1 inhibition has a potential therapeutic benefit for breast cancer patients by increasing the efficacy of conventional chemotherapy. Therefore, MKP-1 inhibition should be developed as a clinically relevant adjuvant therapy, which could provide a novel avenue for therapeutic intervention in combination with chemotherapy in breast cancer patients. Significance: • MKP-1 inhibition with sanguinarine and silencing sensitises breast cancer cells to doxorubicin-induced apoptosis. • The inhibition of MKP-1 with sanguinarine in combination with doxorubicin treatment promotes autophagy induction. • MKP-1 inhibition can have a potential therapeutic benefit for breast cancer patients by increasing the efficacy of conventional chemotherapy.